Diversidade de paronellidae (collembola, arthropleona, entomobryoidea) no nordeste brasileiro, com ênfase em áreas úmidas da caatinga - Meneses, Liugo Fernando (2013)
Paronellidae is among the most diverse and distinctive components of epiedaphic Collembola in tropical countries. However, only 15 species of the family were recorded in Brazil, and only two of them were record in northeast region of the country. This condiction is clearly related to low sampling efforts and lack of specialists working with the group. Due to this reality, this work aimed to study the Paronellidae fauna, under a taxonomic point of view, in six distinct environments in Northeastern Brazil (from Alagoas, Bahia, Ceará, Piauí and Paraíba states), five areas of Caatinga and one from Atlantic Rain Forest biome. Collections were made during the rainy season on each area. The specimens were analyzed under stereomicroscope and mounted in glass slides for microscopy. The specimens identified as Paronellidae had their occurrence recorded and five new species were described. An identification key to the brazilian genera of the family was also prepared. Twelve species of Paronellidae were recorded for the first time to Brazil: Campylothorax mitrai; Lepidonella. sp. nov. 1; Lepidonella sp. nov. 2, Lepidonella sp. nov. 3, Lepidonella sp. nov 4, Lepidonella sp. nov. 5; Dicranocentruga sp. Nov. 1; Dicranocentruga sp. Nov. 2; Dicranocentruga sp. Nov. 3; Paronella sp. nov.1; Serroderus sp. nov.1 and Trogolaphysa. sp. 1, where C. mitrai, Lepidonella. sp. nov 1, Dicranocentruga sp. nov 1, Dicranocentruga sp. nov 2 and Dicranocentruga sp. nov 3 were described. Serroderus and Dicranocentruga genera were recorded for the first time to Brazil. The description of Lepidonella sp. nov 1 also represents the first description of a species of the genus for the country. The data presented show a high potential species richness to Paronellidae, not only in the northeast region, but as in Brazil. In fact, with the records presented in this work, the number of recorded species of Paronellidae in the country increased by 80%. The study of this particular fauna may direct environmental conservation policies, especially in areas of Caatinga